Remaja Perkotaan sebagai Sasaran Masif Terpaan Iklan Rokok di Media Online - Lestari Nurhajati; Kiki Soewarso; Xenia Angelica Wijayanto (Atma Jaya Indonesia Catholic University, Jakarta, 2019)
The number of smokers in Indonesia has increased significantly from year to year, especially among teenagers. Data from the IAKMI Tobacco Support and Support Center in 2014, shows one example, that the number of tobacco smokers in the population is 15 years more than those who chew tobacco. This happened because there were no laws issued by the government which prohibited smoking children while industries advertised their products by increasing through various media, including through online media, targeting teenagers. The purpose of this study is to find out what online media advertises cigarettes targeting teenagers in Indonesia. Creative advertisers emphasize that the advertisements they make are introducing brands, products, or creating awareness for their consumers. But there are also advertisements that direct the action, such as the actions of consumers to buy products. Media exposure theory, especially with the use of online media, is used to see the extent to which cigarette advertisements can penetrate the space and time of young people in urban areas. This study uses a quantitative approach with a method of distributing questionnaires to urban teenagers living in five major cities in Indonesia, namely in Jakarta, Bandung, Semarang, Yogyakarta and Surabaya. The results of this study show that all lines of online media consumed by teenagers are used massively by advertisers of cigarettes. Online media that most often upload cigarette advertisements are YouTube, Website, Instagram and online games.